2012
DOI: 10.1139/h2012-019
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Sedentary Behaviour Guidelines for the Early Years (aged 0–4 years)

Abstract: The Canadian Society for Exercise Physiology (CSEP), with assistance from multiple partners, stakeholders, and researchers, developed the first Canadian Sedentary Behaviour Guidelines for the Early Years (aged 0-4 years). These national guidelines are in response to a call from health and health care professionals, child care providers, and fitness practitioners for guidance on sedentary behaviour in the early years. The guideline development process followed the Appraisal of Guidelines for Research Evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
113
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 155 publications
(123 citation statements)
references
References 31 publications
0
113
0
2
Order By: Relevance
“…The guideline development procedures used here followed comprehensive, rigorous, and transparent processes (Brouwers et al 2010a;Guyatt et al 2011;Tremblay and Haskell 2012) incorporating systematic review findings, consultation findings, compositional analysis findings, and expert, stakeholder, and end-user input as has been done in the past (Tremblay et al 2010b(Tremblay et al , 2011a(Tremblay et al , 2011b(Tremblay et al , 2012a(Tremblay et al , 2012b. Indeed, with experience, the Canadian guideline development process has become even more robust.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The guideline development procedures used here followed comprehensive, rigorous, and transparent processes (Brouwers et al 2010a;Guyatt et al 2011;Tremblay and Haskell 2012) incorporating systematic review findings, consultation findings, compositional analysis findings, and expert, stakeholder, and end-user input as has been done in the past (Tremblay et al 2010b(Tremblay et al , 2011a(Tremblay et al , 2011b(Tremblay et al , 2012a(Tremblay et al , 2012b. Indeed, with experience, the Canadian guideline development process has become even more robust.…”
Section: Discussionmentioning
confidence: 99%
“…Canada has a rich history of producing and promoting evidenceinformed physical activity guidelines (Tremblay et al 2007a(Tremblay et al , 2007b2011a, 2012a) and more recently, sedentary behaviour guidelines (Tremblay et al 2011b(Tremblay et al , 2012b for the promotion of population health. While awareness of the existing guidelines is low (LeBlanc et al 2015), feedback from a variety of stakeholders (e.g., parents, teachers, physical activity professionals, pediatricians) indicates that integrated guidelines that combine the movement behaviours across the whole day would be welcomed and preferred over a series of segregated guidelines (Carson et al 2013a;Faulkner et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Corresponding guidelines for children 5-17 years of age recommend at least 60 minutes of daily moderate-to-vigorous physical activity (MVPA) and no more than 2 hours of daily recreational screen time. 6,7 Nationally-representative data from the 2009-2013 Canadian Health Measures Surveys (CHMS) indicated that 73% of 3-4 year olds met the PA guidelines, but only 22% met the screen time recommendation.…”
mentioning
confidence: 99%
“…For the physical activity guidelines, it is recommended that children aged <1 year are physically active several times a day (5), children aged 2-4 years are physically active at any intensity for at least 180 minutes a day (5), and children and youth aged 5-17 years are physically active at moderate-to vigorous-intensity for at least 60 minutes a day (8). For the sedentary behaviour guidelines, it is recommended children aged <2 years engage in no screen time (6), children 2-4 years engage in under 1 hour a day of screen time (6), and children 5-17 years engage in 2 hours a day or less of recreational screen time (7).…”
mentioning
confidence: 99%